Influence of Chemical Activator (H₃PO₄ and NaOH) on the Characteristics of Coconut Shell-Derived Activated Carbon - Rozalia Rozalia; Deivy Andhika Permata; Ayulian Sara (Poltanesa, 2026)
Activated carbon is an adsorbent material widely utilized in various environmental applications, particularly in water and wastewater treatment due to its excellent adsorption properties. Coconut shell is recognized as a lignocellulosic biomass with significant potential for activated carbon production due to its abundant availability, renewable nature, and high carbon content. However, studies specifically comparing the effect of different chemical activating agents on the physicochemical characteristics of coconut shell-derived activated carbon remain limited. This study aims to compare the characteristics of activated carbon derived from coconut shells chemically activated using two different activating agents, namely phosphoric acid (H₃PO₄) and sodium hydroxide (NaOH). The production process was carried out through a carbonization stage at 700°C for 2 hours, followed by chemical activation using H₃PO₄ and NaOH at concentrations of 5%, 10%, and 15%, respectively. The characterization conducted included analysis of moisture content, ash content, volatile matter, fixed carbon content, and iodine adsorption capacity based on SNI 06-3730-1995 standards. The results indicate that chemical activation can reduce moisture content, ash content, and volatile matter while increasing fixed carbon content. In terms of iodine adsorption capacity, H₃PO₄ at a concentration of 5% was found to be the most effective activator, with a value of 1311.94 mg/g. Activated carbon derived from coconut shells using both H₃PO₄ and NaOH meets the quality standards of SNI 06-3730-1995, indicating its potential use as an adsorbent in water treatment and industrial waste management.